Poor Employment Conditions and Immigrant Health in Europe - Matthew D. Matsaganis; Maria Petraki; Dionysis Balourdos (Social Sciences)
Building on the extant literature and utilizing data from the EU-SILC and the EU-LFS surveys conducted between 2009 and 2023, we empirically investigate the impact of poor employment conditions—associated with insecure or precarious employment—on third-country nationals’ (TCNs’) self-perceived health status (SPH). The role of employment conditions in health is examined by employing indicators of temporary, part-time, and self-employment. Driven by theory and empirical analysis, we also investigate the effects of additional variables, including long-term unemployment. Finally, to probe differences across countries, we examine how the effects of employment conditions on TCNs’ health vary across institutional settings, namely across different types of welfare state. Descriptive statistics and regression analyses of panel data reveal that employment conditions affect immigrants’ SPH and surface significant differences across countries. The estimated country-specific effects point to statistical average differences between Germany and two groups of countries: one showing higher effects (i.e., Austria, Belgium, Denmark, Finland, and France) and another with lower effects (i.e., Greece, Ireland, Italy, and Spain). The welfare model adopted by different countries is a qualitative significant predictor of TCNs’ SPH. We conclude with a discussion of the implications of these findings for future research, but also policy initiatives to improve TCNs’ employment conditions and, consequently, their health and overall well-being.